High-conductivity molybdenum disulfide copper composite material and preparation method thereof

By depositing multiple layers of molybdenum disulfide on the copper foil and performing stacked hot-pressing molding, the problem of poor wetting between molybdenum disulfide and copper is solved, and a molybdenum disulfide copper composite material with high conductivity and stability is prepared.

CN119530754APending Publication Date: 2025-02-28UNIV OF SCI & TECH BEIJING
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411681576.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Poor wetting between molybdenum disulfide and copper leads to a decrease in material strength, and molybdenum disulfide is easily damaged during the preparation of composite materials, and its excellent properties cannot be fully utilized.

Method used

By depositing multiple layers of molybdenum disulfide on both sides of the copper foil, a molybdenum disulfide coated copper foil was formed, and the molybdenum disulfide coated copper foil was heat-pressed by a stacked hot pressing process to prepare a highly conductive molybdenum disulfide copper composite material.

Benefits of technology

It improves the density and tissue uniformity of the material, enhances the interface bonding force, stability and conductivity, and has good process controllability, making it suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The invention discloses a high-conductivity molybdenum disulfide copper composite material and a preparation method thereof, relates to the technical field of composite material manufacturing, and aims to solve the problem of uniform dispersion of molybdenum disulfide layers in the preparation process of the molybdenum disulfide copper composite material. The method comprises the following steps: S1, depositing multiple layers of molybdenum disulfide on the surfaces of the two sides of a copper foil respectively to form a unit material molybdenum disulfide coated copper foil; and S2, at least two pieces of molybdenum disulfide coated copper foil generated in the step S1 are placed in a hot-pressing mold in a hot-pressing cavity, the multiple pieces of molybdenum disulfide coated copper foil are subjected to hot-pressing forming through a lamination hot-pressing technology, and the high-conductivity molybdenum disulfide copper composite material is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite material manufacturing, and in particular to a high-conductivity molybdenum disulfide copper composite material and a preparation method thereof. Background Art

[0002] Pure metals have long been considered to have the highest conductivity at room temperature. Since the first official record of the conductivity of copper about 100 years ago, a large number of studies on highly refined copper metal have only increased the conductivity by about 3%. The widely used International Annealed Copper Standard (IACS) records the conductivity of pure copper at room temperature as 5.8×10 7 S / m, among metals, only silver has a better conductivity than copper (about 108% IACS), but the cost of silver is too high, so copper-based materials have been used as the main conductive material.

[0003] In order to improve the conductivity of copper-based materials, the method of preparing high-purity copper by increasing purity, reducing grain boundaries and reducing defects has gradually approached the physical limit, and the cost has increased significantly, and the technical requirements have become increasingly stringent; and the addition of other alloy materials (such as tin, rare earth elements, etc.) also often has the phenomenon of decreased conductivity due to process instability or copper matrix lattice distortion, which has certain limitations; the use of metallic copper and new materials to prepare high-conductivity copper-based composite materials has attracted extensive research.

[0004] Molybdenum disulfide (MoS2) is a black fixed powder with a metallic luster. Its physical properties include a high melting point (usually around 2375°C), a density of 4.80 g / cm 3 Up to 5.06g / cm 3 The hardness is low, with a Mohs hardness of about 1.0 to 1.5. Molybdenum disulfide exhibits high intrinsic carrier mobility at room temperature, so it is considered to be one of the good candidate materials in the field of micro-nanoelectronic devices. In terms of application fields, molybdenum disulfide is widely used in many fields such as industry, electronics, chemical industry and environmental protection due to its unique physical and chemical properties. As an additive to metal alloys, it can also improve the hardness and wear resistance of the alloy. In the field of electronics, it is used as a basic semiconductor material, conductive material and photoelectric conversion device.

[0005] However, the wettability between molybdenum disulfide and copper is very poor, and the interface bonding between the two is poor, resulting in reduced material strength. In the preparation process of the composite material, the structure of molybdenum disulfide is often destroyed, and the excellent performance of molybdenum disulfide strongly depends on the complete structure. Therefore, the performance of the molybdenum disulfide composite material is often far from the theoretical value, and the mechanical and electrical properties of the metal matrix are reduced due to the different elasticity and capacitance. It is a key problem to solve the uniform dispersion of molybdenum disulfide in the preparation process of molybdenum disulfide copper composite materials. Summary of the invention

[0006] The present invention provides a method for preparing a high-conductivity molybdenum disulfide copper composite material, which comprises the following steps: S1: depositing multiple layers of molybdenum disulfide on both sides of the copper foil to form a unit material molybdenum disulfide coated copper foil; S2: placing at least two pieces of the molybdenum disulfide coated copper foil generated in step S1 in a hot pressing mold in a hot pressing chamber, and using a laminated hot pressing process to hot press multiple pieces of the molybdenum disulfide coated copper foil to obtain a highly conductive molybdenum disulfide copper composite material.

[0007] The present invention is further configured as follows: the thickness of the molybdenum disulfide coated copper foil in step S1 is 10-250 μm.

[0008] The present invention is further configured as follows: in step S1, the number of layers of molybdenum disulfide deposited on the copper foil is 1-150 layers.

[0009] The present invention is further configured as follows: in step S2, the molybdenum disulfide coated copper foil before hot pressing is heated to 600-1100° C. for 20-100 min, then kept at a constant temperature for 20-100 min, and cooled to room temperature after the insulation is completed for 20-100 min.

[0010] The present invention is further configured as follows: in the hot pressing process of step S2, the pressure is 20-200 MPa, the pressurization time is 20-100 min, then the pressure is kept constant for 20-100 min, and after the constant pressure ends, the pressure is reduced to 0 MPa, and the decompression time is 20-100 min.

[0011] The present invention is further configured as follows: the hot pressing chamber in step S2 is maintained in vacuum or filled with argon gas for protection.

[0012] The present invention also provides a high-conductivity molybdenum disulfide copper composite material, which is prepared by the preparation method as described above.

[0013] The beneficial effects of the present invention are as follows: using molybdenum disulfide coated copper foil as a base material, through lamination hot pressing, the prepared molybdenum disulfide copper composite material is more dense, has a uniform structure, good interface bonding, stable performance, and has high thermal and electrical conductivity. At the same time, the method has good controllability and is easy to mass produce. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 A flow chart of the present invention is shown. DETAILED DESCRIPTION

[0015] Those skilled in the art can refer to the content of this article and appropriately improve the process parameters. It is particularly important to point out that all similar replacements and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.

[0016] The present invention provides a method for preparing a high-conductivity molybdenum disulfide copper composite material, comprising the following steps:

[0017] S1: depositing multiple layers of molybdenum disulfide on both side surfaces of the copper foil to form a copper foil coated with a unit material of molybdenum disulfide.

[0018] S2: placing at least two pieces of the molybdenum disulfide coated copper foil generated in step S1 in a hot pressing mold in a hot pressing chamber, and using a laminated hot pressing process to hot press multiple pieces of molybdenum disulfide coated copper foil to obtain a highly conductive molybdenum disulfide copper composite material.

[0019] The thickness of the molybdenum disulfide coated copper foil in step S1 is 10-250 μm.

[0020] The number of layers of molybdenum disulfide deposited on the copper foil in step S1 is 1-150 layers.

[0021] In step S2, the molybdenum disulfide coated copper foil before hot pressing is heated to 600-1100° C. for 20-100 min, then kept at a constant temperature for 20-100 min, and then cooled to room temperature after the insulation is completed for 20-100 min.

[0022] The pressure in the hot pressing process of step S2 is 20-200 MPa, the pressing time is 20-100 min, and then the pressure is kept constant for 20-100 min. After the constant pressure is completed, the pressure is reduced to 0 MPa, and the pressure reduction time is 20-100 min.

[0023] The hot pressing chamber in step S2 is maintained in vacuum or filled with argon for protection.

[0024] Example 1

[0025] The above method is used to prepare a highly conductive molybdenum disulfide copper composite material, and the preparation process is as follows:

[0026] S1: A layer of molybdenum disulfide is prepared on both sides of the copper foil by CVD method to form a unit material molybdenum disulfide coated copper foil, and the thickness of the molybdenum disulfide coated copper foil is 25 μm.

[0027] S2: Take 16 pieces of molybdenum disulfide coated copper foils generated in step S1 and put them into a hot pressing mold in a hot pressing chamber for hot pressing molding.

[0028] Before hot pressing, the material is heated to 900°C for 40 minutes and kept at a constant temperature for 40 minutes, during which time hot pressing is performed. After cooling for 40 minutes, the formed high-conductivity molybdenum disulfide copper composite material is cooled to room temperature.

[0029] During the hot pressing process, the pressing intensity is 50 MPa, the pressing time is 40 min, the constant pressure time is 40 min, and finally the pressure is reduced for 40 min to reduce the pressure to 0 MPa, thereby obtaining a highly conductive molybdenum disulfide copper composite material.

[0030] In this embodiment, the hot pressing chamber maintains 3.0×10 -3 Vacuum degree of Pa.

[0031] The conductivity of the high-conductivity molybdenum disulfide copper composite material prepared in this example was tested by the Van der Pauw method, and the conductivity was measured to be 108.7% IACS.

[0032] Example 2

[0033] The above method is used to prepare a highly conductive molybdenum disulfide copper composite material, and the preparation process is as follows:

[0034] S1: A layer of molybdenum disulfide is prepared on both sides of the copper foil by CVD method to form a unit material molybdenum disulfide coated copper foil, and the thickness of the molybdenum disulfide coated copper foil is 50 μm.

[0035] S2: Take 16 pieces of molybdenum disulfide coated copper foils generated in step S1 and put them into a hot pressing mold in a hot pressing chamber for hot pressing molding.

[0036] Before hot pressing, the material is heated to 900°C for 40 minutes and kept at a constant temperature for 40 minutes, during which time hot pressing is performed. After cooling for 40 minutes, the formed high-conductivity molybdenum disulfide copper composite material is cooled to room temperature.

[0037] During the hot pressing process, the pressing intensity is 60MPa, the pressing time is 40min, the constant pressure time is 40min, and finally the pressure is reduced for 40min to reduce the pressure to 0MPa, thereby obtaining a highly conductive molybdenum disulfide copper composite material.

[0038] In this embodiment, the hot pressing chamber maintains 1.0×10 -3 Vacuum degree of Pa.

[0039] The conductivity of the high-conductivity molybdenum disulfide copper composite material prepared in this example was tested by the Van der Pauw method, and the conductivity was measured to be 109.7% IACS.

[0040] Example 3

[0041] The above method is used to prepare a highly conductive molybdenum disulfide copper composite material, and the preparation process is as follows:

[0042] S1: A layer of molybdenum disulfide is prepared on both sides of the copper foil by CVD method to form a unit material molybdenum disulfide coated copper foil, and the thickness of the molybdenum disulfide coated copper foil is 50 μm.

[0043] S2: Take 16 pieces of molybdenum disulfide coated copper foils generated in step S1 and put them into a hot pressing mold in a hot pressing chamber for hot pressing molding.

[0044] Before hot pressing, the material is heated to 950°C for 40 minutes and kept at a constant temperature for 40 minutes, during which time hot pressing is performed. After cooling for 40 minutes, the formed high-conductivity molybdenum disulfide copper composite material is cooled to room temperature.

[0045] During the hot pressing process, the pressing intensity is 50 MPa, the pressing time is 40 min, the constant pressure time is 40 min, and finally the pressure is reduced for 40 min to reduce the pressure to 0 MPa, thereby obtaining a highly conductive molybdenum disulfide copper composite material.

[0046] In this embodiment, the hot pressing chamber maintains 1.0×10 -3 Vacuum degree of Pa.

[0047] The conductivity of the high-conductivity molybdenum disulfide copper composite material prepared in this example was tested by the Van der Pauw method, and the conductivity was measured to be 112.2% IACS.

[0048] Example 4

[0049] The above method is used to prepare a highly conductive molybdenum disulfide copper composite material, and the preparation process is as follows:

[0050] S1: A layer of molybdenum disulfide is prepared on both sides of the copper foil by CVD method to form a unit material molybdenum disulfide coated copper foil, and the thickness of the molybdenum disulfide coated copper foil is 50 μm.

[0051] S2: Take 16 pieces of molybdenum disulfide coated copper foils generated in step S1 and put them into a hot pressing mold in a hot pressing chamber for hot pressing molding.

[0052] Before hot pressing, the material is heated to 1000°C for 40 minutes and kept at a constant temperature for 40 minutes, during which time hot pressing is performed. After cooling for 40 minutes, the formed high-conductivity molybdenum disulfide copper composite material is cooled to room temperature.

[0053] During the hot pressing process, the pressing intensity is 75MPa, the pressing time is 40min, the constant pressure time is 40min, and finally the pressure is reduced for 40min to reduce the pressure to 0MPa, thereby obtaining a highly conductive molybdenum disulfide copper composite material.

[0054] In this embodiment, the hot pressing chamber maintains 1.0×10 -3 Vacuum degree of Pa.

[0055] The conductivity of the high conductive molybdenum disulfide copper composite material prepared in Example 1 was tested by the Van der Pauw method, and the conductivity was measured to be 111.5% IACS.

[0056] Example 5

[0057] The above method is used to prepare a highly conductive molybdenum disulfide copper composite material, and the preparation process is as follows:

[0058] S1: A layer of molybdenum disulfide is prepared on both sides of the copper foil by CVD method to form a unit material molybdenum disulfide coated copper foil, and the thickness of the molybdenum disulfide coated copper foil is 50 μm.

[0059] S2: Take 16 pieces of molybdenum disulfide coated copper foils generated in step S1 and put them into a hot pressing mold in a hot pressing chamber for hot pressing molding.

[0060] Before hot pressing, the material is heated to 950°C for 40 minutes and kept at a constant temperature for 40 minutes, during which time hot pressing is performed. After cooling for 40 minutes, the formed high-conductivity molybdenum disulfide copper composite material is cooled to room temperature.

[0061] During the hot pressing process, the pressing intensity is 75MPa, the pressing time is 40min, the constant pressure time is 40min, and finally the pressure is reduced for 40min to reduce the pressure to 0MPa, thereby obtaining a highly conductive molybdenum disulfide copper composite material.

[0062] In this embodiment, the hot pressing chamber maintains 1.0×10 -3 Vacuum degree of Pa.

[0063] The conductivity of the high-conductivity molybdenum disulfide copper composite material prepared in Example 1 was tested by the Van der Pauw method, and the conductivity was measured to be 113.2% IACS.

[0064] Example 6

[0065] The above method is used to prepare a highly conductive molybdenum disulfide copper composite material, and the preparation process is as follows:

[0066] S1: 20 layers of molybdenum disulfide are prepared on both sides of the copper foil by CVD method to form a unit material molybdenum disulfide coated copper foil, and the thickness of the molybdenum disulfide coated copper foil is 50 μm.

[0067] S2: Take 16 pieces of molybdenum disulfide coated copper foils generated in step S1 and put them into a hot pressing mold in a hot pressing chamber for hot pressing molding.

[0068] Before hot pressing, the material is heated to 900°C for 40 minutes and kept at a constant temperature for 40 minutes, during which time hot pressing is performed. After cooling for 40 minutes, the formed high-conductivity molybdenum disulfide copper composite material is cooled to room temperature.

[0069] During the hot pressing process, the pressing intensity is 60MPa, the pressing time is 40min, the constant pressure time is 40min, and finally the pressure is reduced for 40min to reduce the pressure to 0MPa, thereby obtaining a highly conductive molybdenum disulfide copper composite material.

[0070] In this embodiment, the hot pressing chamber maintains 1.0×10 -3 Vacuum degree of Pa.

[0071] The conductivity of the high-conductivity molybdenum disulfide copper composite material prepared in this example was tested by the Van der Pauw method, and the conductivity was measured to be 107.2% IACS.

[0072] Example 7

[0073] The above method is used to prepare a highly conductive molybdenum disulfide copper composite material, and the preparation process is as follows:

[0074] S1: Ten layers of molybdenum disulfide are prepared on both sides of the copper foil by CVD method to form a unit material molybdenum disulfide coated copper foil, and the thickness of the molybdenum disulfide coated copper foil is 50 μm.

[0075] S2: Take 16 pieces of molybdenum disulfide coated copper foils generated in step S1 and put them into a hot pressing mold in a hot pressing chamber for hot pressing molding.

[0076] Before hot pressing, the material is heated to 1000°C for 40 minutes and kept at a constant temperature for 40 minutes, during which time hot pressing is performed. After cooling for 40 minutes, the formed high-conductivity molybdenum disulfide copper composite material is cooled to room temperature.

[0077] During the hot pressing process, the pressing intensity is 75MPa, the pressing time is 40min, the constant pressure time is 40min, and finally the pressure is reduced for 40min to reduce the pressure to 0MPa, thereby obtaining a highly conductive molybdenum disulfide copper composite material.

[0078] In this embodiment, the hot pressing chamber maintains 1.0×10 -3 Vacuum degree of Pa.

[0079] The conductivity of the high-conductivity molybdenum disulfide copper composite material prepared in Example 1 was tested by the Van der Pauw method, and the conductivity was measured to be 107.3% IACS.

[0080] Example 8

[0081] The above method is used to prepare a highly conductive molybdenum disulfide copper composite material, and the preparation process is as follows:

[0082] S1: A layer of molybdenum disulfide is prepared on both sides of the copper foil by CVD method to form a unit material molybdenum disulfide coated copper foil, and the thickness of the molybdenum disulfide coated copper foil is 50 μm.

[0083] S2: Take 16 pieces of molybdenum disulfide coated copper foils generated in step S1 and put them into a hot pressing mold in a hot pressing chamber for hot pressing molding.

[0084] Before hot pressing, the material is heated to 600°C for 40 minutes and kept at a constant temperature for 80 minutes, during which time hot pressing is performed. After cooling for 40 minutes, the formed high-conductivity molybdenum disulfide copper composite material is cooled to room temperature.

[0085] During the hot pressing process, the pressing intensity is 75MPa, the pressing time is 40min, the constant pressure time is 40min, and finally the pressure is reduced for 40min to reduce the pressure to 0MPa, thereby obtaining a highly conductive molybdenum disulfide copper composite material.

[0086] In this embodiment, the hot pressing chamber maintains 1.0×10 -3 Vacuum degree of Pa.

[0087] The conductivity of the high-conductivity molybdenum disulfide copper composite material prepared in Example 1 was tested by the Van der Pauw method, and the conductivity was measured to be 104.3% IACS.

[0088] Example 9

[0089] The above method is used to prepare a highly conductive molybdenum disulfide copper composite material, and the preparation process is as follows:

[0090] S1: A layer of molybdenum disulfide is prepared on both sides of the copper foil by CVD method to form a unit material molybdenum disulfide coated copper foil, and the thickness of the molybdenum disulfide coated copper foil is 50 μm.

[0091] S2: Take 16 pieces of molybdenum disulfide coated copper foils generated in step S1 and put them into a hot pressing mold in a hot pressing chamber for hot pressing molding.

[0092] Before hot pressing, the material is heated to 1000°C for 40 minutes and kept at a constant temperature for 80 minutes, during which time hot pressing is performed. After cooling for 40 minutes, the formed high-conductivity molybdenum disulfide copper composite material is cooled to room temperature.

[0093] During the hot pressing process, the pressing intensity is 20 MPa, the pressing time is 40 min, the constant pressure time is 40 min, and finally the pressure is reduced for 40 min to reduce the pressure to 0 MPa, thereby obtaining a highly conductive molybdenum disulfide copper composite material.

[0094] In this embodiment, the hot pressing chamber maintains 1.0×10 -3 Vacuum degree of Pa.

[0095] The conductivity of the high-conductivity molybdenum disulfide copper composite material prepared in Example 1 was tested by the Van der Pauw method, and the conductivity was measured to be 102.6% IACS.

[0096] Example 10

[0097] The above method is used to prepare a highly conductive molybdenum disulfide copper composite material, and the preparation process is as follows:

[0098] S1: A layer of molybdenum disulfide is prepared on both sides of the copper foil by CVD method to form a unit material molybdenum disulfide coated copper foil, and the thickness of the molybdenum disulfide coated copper foil is 50 μm.

[0099] S2: Take 16 pieces of molybdenum disulfide coated copper foils generated in step S1 and put them into a hot pressing mold in a hot pressing chamber for hot pressing molding.

[0100] Before hot pressing, the material is heated to 1000°C for 40 minutes and kept at a constant temperature for 80 minutes, during which time hot pressing is performed. After cooling for 40 minutes, the formed high-conductivity molybdenum disulfide copper composite material is cooled to room temperature.

[0101] During the hot pressing process, the pressing intensity is 200 MPa, the pressing time is 40 min, the constant pressure time is 40 min, and finally the pressure is reduced for 40 min to reduce the pressure to 0 MPa, thereby obtaining a highly conductive molybdenum disulfide copper composite material.

[0102] In this embodiment, the hot pressing chamber maintains 1.0×10 -3 Vacuum degree of Pa.

[0103] The conductivity of the high-conductivity molybdenum disulfide copper composite material prepared in Example 1 was tested by the Van der Pauw method, and the conductivity was measured to be 108.4% IACS.

[0104] Embodiment 11

[0105] The above method is used to prepare a highly conductive molybdenum disulfide copper composite material, and the preparation process is as follows:

[0106] S1: A layer of molybdenum disulfide is prepared on both sides of the copper foil by CVD method to form a unit material molybdenum disulfide coated copper foil, and the thickness of the molybdenum disulfide coated copper foil is 10 μm.

[0107] S2: Take 16 pieces of molybdenum disulfide coated copper foils generated in step S1 and put them into a hot pressing mold in a hot pressing chamber for hot pressing molding.

[0108] Before hot pressing, the material is heated to 950°C for 40 minutes and kept at a constant temperature for 60 minutes, during which time hot pressing is performed. After cooling for 40 minutes, the formed high-conductivity molybdenum disulfide copper composite material is cooled to room temperature.

[0109] During the hot pressing process, the pressing intensity is 50 MPa, the pressing time is 40 min, the constant pressure time is 40 min, and finally the pressure is reduced for 40 min to reduce the pressure to 0 MPa, thereby obtaining a highly conductive molybdenum disulfide copper composite material.

[0110] In this embodiment, the hot pressing chamber maintains 1.0×10 -3 Vacuum degree of Pa.

[0111] The conductivity of the high-conductivity molybdenum disulfide copper composite material prepared in Example 1 was tested by the Van der Pauw method, and the conductivity was measured to be 109.6% IACS.

[0112] Example 12

[0113] The above method is used to prepare a highly conductive molybdenum disulfide copper composite material, and the preparation process is as follows:

[0114] S1: A layer of molybdenum disulfide is prepared on both sides of the copper foil by CVD method to form a unit material molybdenum disulfide coated copper foil, and the thickness of the molybdenum disulfide coated copper foil is 250 μm.

[0115] S2: Take 16 pieces of molybdenum disulfide coated copper foils generated in step S1 and put them into a hot pressing mold in a hot pressing chamber for hot pressing molding.

[0116] Before hot pressing, the material is heated to 950°C for 40 minutes and kept at a constant temperature for 60 minutes, during which time hot pressing is performed. After cooling for 40 minutes, the formed high-conductivity molybdenum disulfide copper composite material is cooled to room temperature.

[0117] During the hot pressing process, the pressing intensity is 50 MPa, the pressing time is 40 min, the constant pressure time is 40 min, and finally the pressure is reduced for 40 min to reduce the pressure to 0 MPa, thereby obtaining a highly conductive molybdenum disulfide copper composite material.

[0118] In this embodiment, the hot pressing chamber maintains 1.0×10 -3 Vacuum degree of Pa.

[0119] The conductivity of the high-conductivity molybdenum disulfide copper composite material prepared in Example 1 was tested by the Van der Pauw method, and the conductivity was measured to be 108.3% IACS.

[0120] Embodiment 13

[0121] The above method is used to prepare a highly conductive molybdenum disulfide copper composite material, and the preparation process is as follows:

[0122] S1: A layer of molybdenum disulfide is prepared on both sides of the copper foil by CVD method to form a unit material molybdenum disulfide coated copper foil, and the thickness of the molybdenum disulfide coated copper foil is 50 μm.

[0123] S2: Take 16 pieces of molybdenum disulfide coated copper foils generated in step S1 and put them into a hot pressing mold in a hot pressing chamber for hot pressing molding.

[0124] Before hot pressing, the material is heated to 1000°C for 40 minutes and kept at a constant temperature for 20 minutes, during which time hot pressing is performed. After cooling for 40 minutes, the formed high-conductivity molybdenum disulfide copper composite material is cooled to room temperature.

[0125] During the hot pressing process, the pressing intensity is 50 MPa, the pressing time is 40 min, the constant pressure time is 40 min, and finally the pressure is reduced for 40 min to reduce the pressure to 0 MPa, thereby obtaining a highly conductive molybdenum disulfide copper composite material.

[0126] In this embodiment, the hot pressing chamber maintains 1.0×10 -3 Vacuum degree of Pa.

[0127] The conductivity of the high-conductivity molybdenum disulfide copper composite material prepared in Example 1 was tested by the Van der Pauw method, and the conductivity was measured to be 107.3% IACS.

[0128] Embodiment 14

[0129] The above method is used to prepare a highly conductive molybdenum disulfide copper composite material, and the preparation process is as follows:

[0130] S1: A layer of molybdenum disulfide is prepared on both sides of the copper foil by CVD method to form a unit material molybdenum disulfide coated copper foil, and the thickness of the molybdenum disulfide coated copper foil is 50 μm.

[0131] S2: Take 16 pieces of molybdenum disulfide coated copper foils generated in step S1 and put them into a hot pressing mold in a hot pressing chamber for hot pressing molding.

[0132] Before hot pressing, the material is heated to 1000°C for 40 minutes and kept at a constant temperature for 100 minutes, during which time hot pressing is performed. After cooling for 40 minutes, the formed high-conductivity molybdenum disulfide copper composite material is cooled to room temperature.

[0133] During the hot pressing process, the pressing intensity is 50 MPa, the pressing time is 40 min, the constant pressure time is 40 min, and finally the pressure is reduced for 40 min to reduce the pressure to 0 MPa, thereby obtaining a highly conductive molybdenum disulfide copper composite material.

[0134] In this embodiment, the hot pressing chamber maintains 1.0×10 -3 Vacuum degree of Pa.

[0135] The conductivity of the high-conductivity molybdenum disulfide copper composite material prepared in Example 1 was tested by the Van der Pauw method, and the conductivity was measured to be 108.6% IACS.

[0136] The specific parameters of Examples 1-14 are shown in the following table: Thickness / μm Number of layers / layer Heating temperature / ℃ Constant temperature time / min Pressure / MPa Electrical conductivity / %IACS Example 1 25 1 900 40 50 108.7 Example 2 50 1 900 40 60 109.9 Example 3 50 1 950 40 50 112.2 Example 4 50 1 1000 40 75 111.5 Example 5 50 1 950 40 75 113.2 Example 6 50 20 900 40 60 107.2 Example 7 50 10 1000 40 75 107.3 Example 8 50 1 600 80 75 104.3 Example 9 50 1 1000 80 20 102.6 Example 10 50 1 1000 80 200 108.4 Embodiment 11 10 1 950 60 50 109.6 Example 12 250 1 950 60 50 108.3 Embodiment 13 50 1 1000 20 50 107.3 Embodiment 14 50 1 1000 100 50 108.6

[0137] Embodiment 15

[0138] The invention also discloses a high-conductivity molybdenum disulfide copper composite material, which is prepared by the preparation method as described above.

[0139] In summary, the present invention uses molybdenum disulfide coated copper foil as a base material, and through lamination hot pressing, the molybdenum disulfide copper composite material prepared is more dense, uniform in structure, good in interface bonding, stable in performance, and has high thermal and electrical conductivity. At the same time, the method has good controllability and is easy to mass produce.

[0140] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be within the scope of protection of the present invention.

Claims

1. A method for preparing a highly conductive molybdenum disulfide copper composite material, characterized in that: The following steps are included: S1: depositing multiple layers of molybdenum disulfide on both sides of the copper foil to form a unit material molybdenum disulfide coated copper foil; S2: placing at least two pieces of the molybdenum disulfide coated copper foil generated in step S1 in a hot pressing mold in a hot pressing chamber, and using a laminated hot pressing process to hot press multiple pieces of the molybdenum disulfide coated copper foil to obtain a highly conductive molybdenum disulfide copper composite material.

2. The method for preparing the highly conductive molybdenum disulfide copper composite material according to claim 1, characterized in that: The thickness of the molybdenum disulfide coated copper foil in step S1 is 10-250 μm.

3. The method for preparing the highly conductive molybdenum disulfide copper composite material according to claim 1, characterized in that: In step S1, the number of layers of molybdenum disulfide deposited on the copper foil is 1-150 layers.

4. The method for preparing the highly conductive molybdenum disulfide copper composite material according to claim 1, characterized in that: In step S2, the molybdenum disulfide coated copper foil before hot pressing is heated to 600-1100° C. for 20-100 min, then kept at a constant temperature for 20-100 min, and cooled to room temperature after the end of the heat preservation for 20-100 min.

5. The method for preparing the highly conductive molybdenum disulfide copper composite material according to claim 1, characterized in that: In the hot pressing process of step S2, the pressure is 20-200 MPa, the pressing time is 20-100 min, and then the pressure is kept constant for 20-100 min. After the constant pressure ends, the pressure is reduced to 0 MPa, and the pressure reduction time is 20-100 min.

6. The method for preparing the highly conductive molybdenum disulfide copper composite material according to claim 1, characterized in that: The hot pressing chamber in step S2 is maintained in vacuum or filled with argon gas for protection.

7. A highly conductive molybdenum disulfide copper composite material, characterized in that: The method is prepared according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Graphene-copper composite material preparation method

    CN109811175A

  • Copper-molybdenum disulfide composite material for electric contact and preparation method thereof

    CN116516206A

  • Preparation method of high-thermal-conductivity and high-electric-conductivity copper boron nitride composite material

    CN118900539A